The Technical Hypothesis of Motivational Interviewing: A Meta-Analysis of MI’s Key Causal Model - Magill, Molly (J Consult Clin Psychol, 2014)
OBJECTIVE: The technical hypothesis of motivational interviewing (MI) posits that therapist implemented MI skills will be related to client speech regarding behavior change and that client speech will predict client outcome. The current meta-analysis is the first aggregate test of this proposed causal model. METHOD: A systematic literature review, using stringent inclusion criteria, identified k = 16 reports describing 12 primary studies. Review methods calculated the inverse-variance-weighted pooled correlation coefficient for the therapist to client and the client to outcome paths across multiple targeted behaviors (i.e., alcohol or illicit drug use, other addictive behaviors). RESULTS: Therapist MI-consistent skills were correlated with more client language in favor of behavior change (i.e., change talk; r = .26, p < .0001), but not less client language against behavior change (i.e., sustain talk; r = .10, p = .09). MI-inconsistent skills were associated with less change talk (r = −.17, p = .001) as well as more sustain talk (r = .07, p = .009). Among these studies, client change talk was not associated with follow-up outcome (r = .06, p = .41), but sustain talk was associated with worse outcome (r = −.24, p = .001). In addition, studies that examined composite client language (e.g., an average of negative and positive statements) showed an overall positive relationship with client behavior change (r = .12, p = .006; k = 6). CONCLUSIONS: This meta-analysis provides an initial test and partial support for a key causal model of MI efficacy. Recommendations for MI practitioners, clinical supervisors, and process researchers are provided.